Der Unernst des Kitsches: Die Ästhetik des laxen Blicks auf die Welt - Ra, Yushin (transcript, 2016)
Kitsch is more than it is given credit for. It is not only an aesthetic reaction to industrialised society or merely a progressive means of expression – instead, it stands for a specific aesthetic worldly sensibility. Yushin Ra pursues it further and shows that kitsch generates a frivolity through the peculiar manner of its interaction on a meta-communicative level and its superficial communication. It hovers on the border of both, thereby creating an ambiguity that gives rise to a definitive scepticism as to the seriousness of the product on the part of its recipients. This flippant attitude represents the view that there is a niche in the world that will not be reached by the force of reason or practical action.